Working-week flexibility: implications for employment and productivity - Institut für Weltwirtschaft, Kiel; Osuna, Victoria (Leibniz, 2013)
"The aim of this paper is to analyse and discuss the heterogeneity level between the old and new EU member states in terms of welfare state development. In order to discuss the research questions, we performed the cluster analysis that provides the overall survey of the welfare state development and besides that, the results were divided into four dimensions: demographic, economic, institutional and social. In comparison with the thematic literature, we modified the dimensions, including our original institutional dimension, and added a dynamic point of view. The cluster analysis resulted in the existence of three clusters: Core cluster, Periphery cluster and Eastern cluster. The Eastern cluster is still relatively stable and covers in a total of nine of the ten Central and Eastern European countries that were included in the analysis: Bulgaria, the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Romania and Slovakia (hence apart from Slovenia). On the other hand, using the dimensional approach, the CEE countries were grouped together with the old EU member countries, both from the Core cluster and from the Periphery cluster, within the economic and institutional dimensions. Therefore, we conclude that the new EU member countries, nowadays, do not form an internally homogenous group in terms of the features of their welfare state."